2018
DOI: 10.1186/s12905-018-0584-2
|View full text |Cite
|
Sign up to set email alerts
|

Depression, sexual dysfunction and sexual quality of life in women with infertility

Abstract: BackgroundWomen suffering from infertility are at higher risk of experiencing psychological problems. Sexual function and sexual related quality of life is not considered as it should be. We designed this study to assess depression, sexual function and sexual quality of life in Iranian women with infertility.MethodsTwo hundred and sixty four individuals participated in the study (115 healthy controls, 78 with primary and 71 with secondary infertility). All participants were asked to fill a valid and reliable P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 19 publications
5
56
2
11
Order By: Relevance
“…To the best of our knowledge, this is the rst study addresses a psychological disorder, depression, in infertile women. A growing body of evidence emphasized on psychological aspect of infertility in women (1,6,10,(17)(18)(19)(20)(21)(22)(23). Infertility is a source of stress for couples who are unable to conceive and depression was most commonly reported and its incidence varied among societies and countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the rst study addresses a psychological disorder, depression, in infertile women. A growing body of evidence emphasized on psychological aspect of infertility in women (1,6,10,(17)(18)(19)(20)(21)(22)(23). Infertility is a source of stress for couples who are unable to conceive and depression was most commonly reported and its incidence varied among societies and countries.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), approximately 60-80 million individuals have a type of infertile couples worldwide (9) . Consequently, nearly 40% of individuals who seek infertility treatment are unable to achieve pregnancy (10). In Palestine, no accurate data about prevalence of infertility among couples.…”
Section: Introductionmentioning
confidence: 99%
“…Although infertility is considered as a catostrophic phenomen for couples worldwide, studies show that the adverse psychological effects of infertility are found to be greater among women than that of men (2).This is because motherhood has traditionally been accepted as an essential role for women in Iranian culture. Many times, an infertile woman believes she cannot imagine a childless life while his spouse may express a different feeling (10,11). In general, infertile women are more likely than men to seek for treatment for which the female gender or the couple go through emotional and nancial hardship (12).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported a great deal of complications such as fatigue, depression, stress, and lack of selfesteem as psychological consequences of infertility among infertile women (11,13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation